Pre-service English teachers’ motivation to pursue a career in teaching viewed from speaking self-efficacy - Hartono Hartono; Nani Hidayati; Wiyaka Wiyaka (Institute of Advanced Engineering and Science, 2023)
Previous research on pre-service teachers’ motivation to pursue a career in teaching found different results. Some research found altruistic motivation dominant in determining career decisions, while others suggest extrinsic or intrinsic motivation. The current study extended the topic by relating pre-service English teachers’ motivation to teach to English-speaking self-efficacy. There were 94 pre-service English teachers of different semesters participated in this study. Data were collected with a Likert-type questionnaire. Pre-service English teachers have a high motivation to pursue a career in teaching, and extrinsic motivation was the most dominant motive. The nobility of the profession, sustainability of job demand, inspiration from the teachers, and flexible working hours are among the extrinsic motives. The pre-service teachers also have a high level of English-speaking self-efficacy. However, they still have problems with anxiety, the use of idioms, the use of accurate grammar and vocabulary, and fluency. Between motivation to teach and their speaking self-efficacy lies a significant positive correlation at a moderate level. This moderate level of the relationship suggests that English-speaking self-efficacy is not a determining factor in motivating pre-service English teachers to have a career in teaching. Consequently, some English teachers may have inadequate proficiency in the language they teach.